THE COVID-19 PANDEMIC:: INVOKING THE FAMINE AND PESTILENCE CLAUSE TO BE PAIRED WITH THE MEDICINE CHEST CLAUSE FROM THE NUMBERED TREATIES (Canadian Journal of Native Studies, 2026)
The COVID-19 pandemic requires specific treaty-based strategiesto address the unique position of First Nations communitiesacross Canada within treaty territories. A treaty-basedapproach is necessary to recognize certain provisions set outin the Numbered Treaties in Canada. These provisions includethe Famine and Pestilence Clause and Medicine Chest Clause,both clauses were agreed to during the Treaty #6 signing in1876. In the Famine and Pestilence Clause the Crown agreed toprovide assistance to the “Indian” Peoples in the event of anycalamity that came upon them, such as locust raids, storms,starvation, or disease. The Medicine Chest Clause implementsthe means to provide the medical aid to go along with theFamine and Pestilence Clause. The Government of Canadahas a legal obligation to immediately invoke the Famine andPestilence Clause together with the Medicine Chest Clause ina strategy to address the spread of the COVID-19 pandemic.